Aqueous extract of Securidaca longipendunculata Oliv. and Olax subscropioidea inhibits key enzymes (acetylcholinesterase and butyrylcholinesterase) linked with Alzheimer's disease in vitro - Jamiu A. Saliu; Ayodeji A. Olabiyi (Taylor & Francis Group, 2017)
Context: Plants have historically been used to treat neurodegerative diseases which include Alzheimer's disease. Objective: This study investigated the antioxidant properties and inhibitory effect of aqueous extracts of Securidaca longipendunculata root and Olax subscropioidea leaf on the cholinergic system in rat brain in vitro. Materials and methods: Aqueous extracts (1:20 w/v) of S. longipendunculata root and O. subscropioidea leaf was prepared and the ability of the extract to inhibit the activities of acetylcholinesterase and butyrylcholinesterase was evaluated as well as antioxidants as typified by 2,2-azino-bis-(3-ethylbenthiazoline-6-sulphonic acid (ABTS•) radical scavenging ability and Fe chelation spectophotometrically. Results: ABTS• radical scavenging ability showed that S. longipendunculata (0.075 Mmol TEAC/100 g) had a higher scavenging ability than O. subscropioidea (0.07 Mmol TEAC/100 g). Also, the Fe2+ chelating ability of both extracts revealed that S. longipendunculata (IC50 = 105.57 g/mL) had a significantly (p < 0.05) higher Fe2+ chelating ability than O. subscropioidea (IC50 = 255.84 g/mL). Extracts of S. longipendunculata and O. subscropioidea inhibited acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) activities. However, S. longipendunculata (IC50 = 108.02 g/mL) has the higher AChE inhibitory activity than O. subscropioidea (IC50 = 110.35 g/mL). Also, both extracts inhibit BChE activity in vitro but S. longipendunculata (IC50 = 82.55 g/mL) had a higher BChE inhibitory activity than O. subscropioidea (IC50 = 108.44 g/mL). Discussion and conclusions: The mechanism by which S. longipendunculata root and O. subscropioidea leaf perform their anti-Alzheimer's disease activity may be by their inhibition on the key enzymes linked to this disease.